ВИБІР КІЛЬКОСТІ ТА МІСЦЬ ВСТАНОВЛЕННЯ ІНДИКАТОРІВ ПОШКОДЖЕНЬ НА РОЗПОДІЛЬНІЙ ЛІНІЇ ЯК ЗАДАЧА КОМБІНАТОРНОЇ ОПТИМІЗАЦІЇ - Парус, Є.В.; Блінов , І.В.; Бець, О.Ю. (Інститут електродинаміки НАН України, Київ, 2016)
In the article the problem statement of fault indicators location and quantity selection on distribution line and methods of its solving are studied. The objective function is performed as the problem of maximization of charges differential of power supply utility when exploiting distribution line with/without fault indicators. The hierarchical nesting of combinatorial problems which is necessary for calculation of maximum of objective function is shown. The rules of thumb set for reducing of combinatorial level of the problem is proposed. References 6.